Boron trifluoride etherate as a catalyst precursor for coliquefaction of coal and plastics at the mild conditions. (2015) - Du, Kun; Wu, Hong; Li, Yu; Huang, Lin; Zhang, Jianxin; Wang, Daoping
The objective of this work is the study of boron trifluoride etherate (C4 H10 BF3 O, a kind of Lewis acid) as a catalyst to depolymerise coal. Coliquefaction of coal and low-density polyethylene (LDPE) using C4 H10 BF3 O with different weight ratio of coal and LDPE were carried out at 370°C. The similar coliquefaction using C4 H10 BF3 O at 200°C, and the similar coliquefaction using ammonium molybdate [(NH4 )2MoO4 ] as catalyst at 370°C were performed for comparison. The result indicates that C4 H10 BF3 O plays a significant role in depolymerisation of coal at 370°C other than 200°C, and oil yield increased approximately 30% when the temperature increased from 200°C to 370°C. The main reason is that coal has a deeper level of cracking at higher temperature. The hexane soluble, hexane insoluble-tetrahydrofuran (THF) soluble and residue organic parts after coliquefaction were analysed by molecular weight, FT-IR, 1 H-NMR and 13 C-NMR to get confirmatory results. [Received: April 29, 2013; Accepted: November 8, 2013]